THE IMPACT OF DIGITAL TECHNOLOGIES ON LEARNING THE ENGLISH LANGUAGE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
In recent years, digital technologies have transformed the way English is taught and learned across the world. The integration of online platforms, mobile applications, interactive tools, and artificial intelligence has significantly improved learners’ access to educational resources and enhanced language acquisition processes. This article examines how digital tools influence vocabulary development, listening and speaking skills, grammar learning, and overall learner motivation. The study highlights both the advantages and the challenges associated with the use of digital technologies in English language education, offering recommendations for effective implementation in modern learning environments.